Innovating instruction of Malay grammar through a word list program - Isam, Hishamudin (Canadian Center of Science and Education, 2013)
The dilemma of teaching and/or learning grammar in a language that is often considered ‘dry’ and dull often happens not just to students, but also to teachers.One of the factors that contribute to this problem is the lack of appeal that could intrigue students to learn, understand and gradually master the grammar of a language. Consequently, the teaching and learning of grammar which ought to be “alive” will become irrelevant, namely to the new generation of IT literate students.Thus, this study attempts to present a new method of teaching and learning grammar, taking into account the interests and preferences of students who are quite familiar to the world of information technology.If previously the teaching and learning of grammar, particularly the grammatical system, was closely related to the description of rules (right and wrong) and formulas (rules) with the aid of grammar and dictionary, the new method proposed will expose students to a computer software program based on the list of words that can assist students in understanding the grammar system more comprehensively, effectively and interestingly. For a start, this study will show how the antconc word list program enables students to understand the complex meaning of a particular lexeme selected from the corpus.Students will then learn to produce sentences from the complex meanings which they have identified from the word list program.